Development of a research skills test instrument for high school learners in the context of climate change integrated with ecosystems - Dini Nurani Rahmawati; R. Riandi; Rini Solihat (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Student participation in Indonesia in activities that develop research skills, such as OPSI (Olimpiade Penelitian Siswa Indonesia or Indonesian Student Research Olympiad), remains low. A preliminary study to gather teachers' perceptions regarding research skills was also conducted by the author using a questionnaire; the results indicated that not many teachers have implemented research skills training in learning activities. This research aims to develop an instrument used to assess students' research skills. The study employs research and development methods consisting of define, design, develop, and dissemination stages. During the define stage, content and construct validity tests were conducted on research skill questions. Subsequently, the test item construction was developed and revised. A trial was carried out for analysis regarding internal validity and reliability. The results of this study consist of a set of research skills test instruments that include 6 aspects of research skills adapted and modified from the research skills development (RSD) assessment matrix by Willison & O’Regan, and subsequently developed into 40 question items to measure the aspects of research skills, namely: Initiating and Explaining Research Problems, Finding and Generating Information/Data, Evaluating and Reflecting on the Research Process, Organising Data Results and Managing the Research Process, Analysing and Synthesising Research Results, as well as Communicating and Applying Research Results. The questions are presented in the context of climate change. The results of expert validation and trials indicate that all of these questions are valid and reliable. The results obtained from expert validation scored 4.4 and above, while the trial values showed that all questions had significant and very significant values and a reliability of 0.93. Therefore, the results of this study recommend the use of this test tool for research in measuring students' research skills.